Enhancing Vocabulary Mastery and Motivation Using Wordwall Games: Implications for Junior High Education - Rury Rubykania; Sholeh Hidayat; Isti Rusdiyani (Tarbawi: Jurnal Keilmuan Manajemen Pendidikan, 2025)
This study aims to explore the effectiveness of using WordWall, a game-based learning platform, in improving the vocabulary acquisition of grade VII students at SMPN 5 Pandeglang. A qualitative case study methodology was employed to gather data via observation, semi-structured interviews, and document analysis. The results showed that the implementation of WordWall significantly increased students' participation in learning, improved vocabulary retention, and increased learning motivation. A total of 80% of students stated that this method was more fun than the traditional method, while 75% of students reported an improvement in their vocabulary recall. Teachers also found that WordWall helped create a more dynamic and interactive learning environment. Thus, the integration of interactive technologies such as WordWall in English teaching can be an effective solution in improving students' vocabulary skills and promoting more meaningful learning. Therefore, the integration of interactive technology in teaching is highly recommended as it can create a more engaging and meaningful learning experience for students.